2013
DOI: 10.1007/s11115-013-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Control—Norwegian Ministries’ and Agencies’ Reactions to Performance Audit

Abstract: Ministries are increasingly subject to control, primarily by State Audit Institutions'. This control is assumed to contribute to improvement. Based on survey data from 353 civil servants in Norway this article analyses the ministries' and agencies' responses to the SAIs control. The analysis shows that civil servants in the ministries tend to be less positive to performance audit than civil servants in the agencies. Top executives, irrespective of administrative level, were more negative than middle managers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
0
23
2
1
Order By: Relevance
“…Though substance auditing may take many forms, and may concern many different aspects of an organization's activities, a common way of describing substance auditing is by referring to auditing of the three Es (see, e.g. Bringselius, ; Pollitt et al., ; Reichborn‐Kjennerud, ). Therefore, audits of the three Es were considered to be relevant examples of substance auditing in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though substance auditing may take many forms, and may concern many different aspects of an organization's activities, a common way of describing substance auditing is by referring to auditing of the three Es (see, e.g. Bringselius, ; Pollitt et al., ; Reichborn‐Kjennerud, ). Therefore, audits of the three Es were considered to be relevant examples of substance auditing in this study.…”
Section: Methodsmentioning
confidence: 99%
“…One common and well‐recognized attempt to narrow the focus of substance auditing is found in the International Organisation of Supreme Audit Institutions’ (INTOSAI) (, ) guidelines, which suggest that a PA should establish whether public organizations operate in a manner that keeps costs low (Economy), makes the most of available resources (Efficiency), and achieves its stipulated goals (Effectiveness) (see also, e.g. Pollitt et al., ; Reichborn‐Kjennerud, ). However, even though the concepts of Economy, Efficiency and Effectiveness (the three Es) may clarify the scope of substance auditing to some extent, the concepts are but a perspective of the ephemeral and by no means a readily auditable performance phenomenon.…”
Section: The Challenge Of Substance Auditing – Insights From the Litementioning
confidence: 99%
“…Furthermore, earlier research found that actors “tend to be become more negative if they are exposed to many performance audits” (Reichborn‐Kjennerud, , p. 28). The interviews carried out for the current article showed that many ministries and governmental organizations have specific people assigned to deal with audits and ombudsman investigations.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Research on the impact and value of performance auditing on public sector organisations (Bawole & Ibrahim, 2015;Raudla, Taro, Agu, & Douglas, 2015) has been a leading field of inquiry in recent years. Whether performance auditing has an impact on the improvement of auditee entities (Yang, 2012), its usefulness in the eyes of auditees (Reichborn-Kjennerud, 2015), the consequences of performance auditing (Reichborn-Kjennerud & Vabo, 2017), overall impact of performance auditing as a result of the implementation of audit recommendations (Hoque & Pearson, 2018), changes it brings in the audited organisations (Morin, 2014), and the contributing factors for those changes (Siddiquee, 2014), still merit further research from the aspect of follow-up on performance auditing issues. Therefore, in ascertaining follow-up effectiveness, one must also consider the practices by which it is being governed.…”
Section: Introductionmentioning
confidence: 99%